2012
DOI: 10.1080/01635581.2012.713161
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiinflammatory Kinetics of Curcumin as a Potential Antimucositis Agent in Cancer Patients

Abstract: The antiinflammatory agent curcumin (diferuloylmethane) has a potential to mitigate cancer therapy-induced mucositis. We assessed the in vitro extent of its bactericidal activity and determined the kinetics of its antiinflammatory effect on pharyngeal cells. Bactericidal activity was assessed using the LIVE/DEAD® Kit after 4 h of exposure to curcumin (50-200 μM) in 18 oropharyngeal species commonly associated with bacteremia in febrile neutropenia. Moraxella catarrhalis or its outer membrane vesicles were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…37 Histopathological observations indicate that in the cohorts where turmeric was applied, increased levels of reepithelialization of epidermis; migration of myofibroblasts, fibroblasts, and macrophages to the wound bed; promotion of neovascularization and greater deposition of collagen was pronounced and that this effect was mediated by increased levels of transforming growth factor-β1. 37 Additionally, studies have also shown that turmeric and its principal compound curcumin possess antiinflammatory 66 effects, promote reepithelialization, 67 and enhance healing of wounds created in skin exposed to radiation. [36][37][38][39] In lieu of all these observations it can be postulated that the beneficial effects of turmeric in preventing radiation-induced mucositis can be best explained by its antiinflammatory, antioxidant, antimicrobial, modulating cytokines, and by enhancing wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…37 Histopathological observations indicate that in the cohorts where turmeric was applied, increased levels of reepithelialization of epidermis; migration of myofibroblasts, fibroblasts, and macrophages to the wound bed; promotion of neovascularization and greater deposition of collagen was pronounced and that this effect was mediated by increased levels of transforming growth factor-β1. 37 Additionally, studies have also shown that turmeric and its principal compound curcumin possess antiinflammatory 66 effects, promote reepithelialization, 67 and enhance healing of wounds created in skin exposed to radiation. [36][37][38][39] In lieu of all these observations it can be postulated that the beneficial effects of turmeric in preventing radiation-induced mucositis can be best explained by its antiinflammatory, antioxidant, antimicrobial, modulating cytokines, and by enhancing wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing head and neck radiotherapy, pain and decreased oral function may persist long after the conclusion of therapy. Fractionated radiation dosage increases the risk of mucositis to >70% of patients in most trials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical isolates included Moraxella catarrhalis ATCC 25238 [4], M. catarrhalis O35E [6], Streptococcus pneumoniae serotype 6B [5] and nontypable Haemophilus influenzae [5]. The human pharyngeal cell line Detroit 562 (ATCC CCL 138) was maintained in Eagle’s minimal essential medium (MEM, Invitrogen, Basel, Switzerland) supplemented as indicated with heat-inactivated fetal calf serum (FCS), 2 mM L-glutamine, 1 mM sodium pyruvate (Sigma, St. Louis, MO), 1x nonessential amino acids (Sigma), 100 U/ml penicillin, and 100 μg/ml streptomycin at 37°C in an atmosphere containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Interleukin (IL)-8 was determined using a commercially available ELISA kit according to the manufacturer’s protocol (R&D Systems, Minneapolis, MN). For determination of additional cytokines and chemokines in the same cell supernatants the Luminex® xMAP® technology was used [5]. Milliplex map kits (Milliplex Corporation) were used for microsphere-based multiplex immunoassays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation